2013
DOI: 10.1021/jm301819k
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Antivirulents Targeting the Iron-Regulated Heme Oxygenase (HemO) ofP. aeruginosa

Abstract: Bacteria require iron for survival and virulence and employ several mechanisms including utilization of the host heme containing proteins. The final step in releasing iron is the oxidative cleavage of heme by HemO. A recent computer aided drug design (CADD) study identified several inhibitors of the bacterial HemOs. Herein we report the near complete HN, N, CO Cα and Cβ chemical shift assignment of the P. aeruginosa HemO in the absence and presence of inhibitors (E)-3-(4-(Phenylamino)phenylcarbamoyl) acrylic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 44 publications
(108 reference statements)
2
36
0
Order By: Relevance
“…30 Selected compounds included those containing hydrophilic or lipophilic substitutions and individually resolved protons ( 9, 12 , and 17 ) as well as the largest substitution, compound 24 . Integration of the difference peaks allows for comparison of relative magnetization transfer, and therefore degree of interaction, of each proton with HemO (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Selected compounds included those containing hydrophilic or lipophilic substitutions and individually resolved protons ( 9, 12 , and 17 ) as well as the largest substitution, compound 24 . Integration of the difference peaks allows for comparison of relative magnetization transfer, and therefore degree of interaction, of each proton with HemO (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the methoxy protons of compound 17 show much less interaction with HemO than the aromatic protons, much like the N -methyl protons of compound 1 . 30 The largest compound, 24 , contains two sets of aromatic protons with overlapping signals that cannot be resolved. The two unique signals, for the benzylimine proton and the para-position proton, show the largest relative interactions at 100% and 82%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined, these studies indicate that the heme acquisition pathway of P. aeruginosa is capable of regulating gene expression by at least two distinct mechanisms. While the impacts of these systems on virulence gene expression are not yet known, earlier studies showed that inhibition of HemO attenuated virulence of P. aeruginosa in a Caenorhabditis elegans model of infection [68]. More studies are clearly needed to understand the full impact of heme-mediated gene regulation during P. aeruginosa pathogenesis.…”
Section: Coordinated Regulation Of Virulence and Iron Uptakementioning
confidence: 99%
“…Through in silico drug design and model simulations, two chemical entities were identified as inhibitors of P. aeruginosa heme oxygenase. One of these compounds prolonged the lifespan of infected nematodes and decreased bacterial colony forming units in the C. elegans intestine, albeit showing poor antimicrobial activity in vitro (Hom et al, 2013). Recently, Zhu et al (2015) used the C. elegans model to characterize an inhibitor of LasB, a vital virulence factor of P. aeruginosa .…”
Section: Identification Of Novel Anti-infectivesmentioning
confidence: 99%